2021
DOI: 10.3390/biomedicines9111531
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis in Cancer and Potential Use of Omega-3 Free Fatty Acids in Its Management: A Review

Abstract: Oral mucositis (OM) is a painful condition caused by chemotherapeutic or radiotherapeutic cancer treatments, occurring in patients with different tumour characteristics and locations. OM greatly impacts a patient’s quality of life and cancer recovery. Current OM management strategies are not providing sufficient prevention and treatment; new approaches to injury management are needed. Studies on the benefit of omega-3 free fatty acids (FFA) in human health have increased significantly in recent years. FFA prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
(110 reference statements)
2
6
0
Order By: Relevance
“…Previous studies revealed that both DHA and EPA affect CASP3 and, consequently induction of apoptosis (Sauer et al, 2005;Xue et al, 2017). Also, the BCL-2 family proteins are essential in Omega-3-induced cell death (Çetin et al, 2021;Lessa et al, 2021;Ma et al, 2021) suppressed by the L. plantarum. Also, the mRNA level of the BAX gene was upregulated, while BCL-2 was downregulated in C26 cells after being treated with either suspension of L. plantarum or bacteria extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that both DHA and EPA affect CASP3 and, consequently induction of apoptosis (Sauer et al, 2005;Xue et al, 2017). Also, the BCL-2 family proteins are essential in Omega-3-induced cell death (Çetin et al, 2021;Lessa et al, 2021;Ma et al, 2021) suppressed by the L. plantarum. Also, the mRNA level of the BAX gene was upregulated, while BCL-2 was downregulated in C26 cells after being treated with either suspension of L. plantarum or bacteria extract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that both DHA and EPA affect CASP3 and, consequently induction of apoptosis (Sauer et al, 2005 ; Xue et al, 2017 ). Also, the BCL‐2 family proteins are essential in Omega‐3‐induced cell death (Çetin et al, 2021 ; Lessa et al, 2021 ; Ma et al, 2021 ). Our findings are in line with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, Omega-3 PUFAs health benefits have been outlined and escalated in multidisciplinary systemic diseases such as diabetes, cardiovascular diseases and cancer (8,9). They have also been shown to play critical roles in tissue homeostasis restoration and inflammation mitigation in a variety of oral diseases, that include oral mucositis (34). Thus, the main objective of this study was to evaluate the effect of Omega-3 topical emulgel on RIOM prevention in HNC patients treated by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (PUFAs) are recognised as immunonutrients with diverse biological effects, including roles in cell signalling, cell membrane structure, inflammation resolution, and acting on G protein-coupled receptors [83]. While commonly used in the nutritional therapy of cancer patients, the 2017 European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines primarily focus on omega-3 PUFAs for treating cancer-related cachexia, overlooking their potential benefits for managing other cancer-related complications such as anorexia, pain, depression, paraneoplastic syndromes, and mucositis [83,84].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%